Visual stress associated with reading difficulties: prevalence and intervention in elementary school students (Research, Society and Development, 2021)
Visual stress is defined as a neuronal-based dysfunction of visual processing, with a deficit in the magnocellular system and in the primary visual cortex. It is characterized by visual-perceptual distortions and progressive visual discomfort in reading. The present study verified the prevalence of visual stress among students from 3rd and 4th grades of elementary school (7 to 10 years old) with reading difficulties, as well as investigated the effect of the use of overlays on reading ability. All eligible participants (n = 58) had reading difficulties and adequate binocular visual acuity. Overlays were selected and distributed to students for use for three months. The Visual Reading Perception Scale, the Reading Rate Test and the Reading Test - Comprehension and Sentence characterized the pre- and post-intervention conditions. The results indicated a 12% prevalence of visual stress (severe symptoms). After the intervention, it was verified that the use of spectral slides promoted an increase in sentence comprehension and reading rate. Thus, it is concluded that visual stress is a very prevalent disorder among children with reading difficulties and that overlays are an effective method of intervention to reduce visual stress in reading.